53 Compassionate communities in north wales: a service evaluation. Issue 3 (1st September 2017) - Watt, Bethany; Hiscock, Julia; Poolman, Marlise; Livingstone, Tracy
Abstract : Aim: To evaluate hospice-supported, volunteer-led community befriending services in North Wales operating within the Compassionate Communities model. Methods: Five semi-structured, qualitative interviews lasting 1–2 hours were conducted with facilitators of current hospice-supported community befriending services in North Wales. These comprised the four volunteer coordinators, two at each site, in addition to the hospice lead for the facilitation of these services. Ten (out of a total of nineteen) volunteers involved with the befriending services completed an online (or paper if preferred) survey about their current activities within, and views on, the befriending services. Data from the qualitative interviews was fully transcribed verbatim, and subsequently combined with qualitative data from the volunteer survey and analysed using the Framework approach. Descriptive statistics were used to provide frequency data (counts, percentages) from the volunteer survey where the answer format provided pre-determined responses. Results: Initial analysis of the results has provided an understanding of the development and operation of these community-led services, and has given insight into perceived barriers to and facilitators of their optimal functioning. It has revealed duality of opinion about the role of the hospice and the role of the community within the befriending services, most notable in the coexistence of views expressed regarding the need to be protected and guided by the hospice, and the desire to be free from the confines of hospice-imposed regulations and the medical model of care. We will present the results of the full analysis and consider implications for hospices nationwide in facilitating the development of Compassionate Communities.